Selling a 'Just' War - Butler, M. author. aut Link
XIII, 284 p.
Keywords: Butler sheds light on how American political leaders sell the decision to intervene with military force to the public and how a just war frame is employed in US foreign policy. He provides three post-Cold War examples of foreign policy crises: the Persian Gulf War (1990-91), Kosovo (1999), and Afghanistan (2001).